Customer Experience and E-Wom Effects on Brand Image and Patient Revisit Intention at Dental Clinics In Bogor - Siti Holilah; Agus Setyo Pranowo; Herdiyana (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of customer experience and electronic word of mouth (e-WOM) on brand image and their impact on patient revisit intention at dental clinics in Bogor City. The study was motivated by the increasingly competitive dental service industry, the growing role of digital reviews, and the need to strengthen patient retention in dental healthcare services. A quantitative explanatory approach was employed using an online survey of 200 patients who had visited dental clinics in Bogor City at least once. The data were analyzed using descriptive statistics and Structural Equation Modelling with LISREL 8.80. The results show that customer experience has a positive and significant effect on brand image and patient revisit intention. e-WOM also has a positive and significant effect on brand image and revisit intention. Furthermore, brand image positively affects revisit intention and partially mediates the relationship between customer experience and e-WOM on revisit intention. These findings indicate that dental clinics should integrate service experience management, credible digital reputation, and consistent brand image development to increase patient retention.